Knowledge and Attitudes of Nurses and Doctors Toward Nurse Prescribing - Abdulelah Marzouq Saqr Alotaibi; Mansour Saud Fahhad Alharbi; Khald Ziyad Qutaym Alotaibi; Saif Eid Alharbi; Abdullah Hudairem Muaybid Al Harbi; Alanoud Yahya Ali Alsalhi; Motlaq Hazaa Mutlaq Algidani; Turki Mana Khatim Alrashdi; Khaled Abdullah Saleh Al-Dawas; Hayyan Dahim H Alharbi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Background: The expanding role of nurses in healthcare has increasingly included prescribing medication, a practice that varies across healthcare systems. While nurse prescribing has been associated with improved healthcare delivery, there is limited research on the knowledge, attitudes, and readiness of critical care nurses and physicians regarding this practice. This study aims to explore these factors in critical care settings. Methods: A descriptive, cross-sectional study was conducted with 280 nurses and physicians working in critical care units. Participants were randomly selected from six teaching hospitals. Data were collected using a three-part questionnaire assessing demographic information, knowledge of nurse prescribing, and attitudes toward the practice. Knowledge was evaluated with a true/false questionnaire, while attitudes and readiness were assessed using Likert scales. Data analysis was performed using SPSS V.22. Results: The mean knowledge score for nurses was 14.76 (SD = 2.13), compared to 16.92 (SD = 1.68) for physicians (p < 0.05). Nurses had a mean attitude score of 36.24 (SD = 5.71), while physicians scored 40.12 (SD = 4.81) (p < 0.05). Nurses’ readiness for prescribing had a mean score of 39.12 (SD = 4.47), and physicians had a mean score of 42.34 (SD = 3.88) (p < 0.05). Significant positive correlations were found between knowledge and attitudes (r = 0.45, p < 0.01), and between attitudes and readiness (r = 0.51, p < 0.01). Conclusion: Both nurses and physicians generally demonstrated positive knowledge and attitudes toward nurse prescribing, with physicians showing slightly better knowledge and readiness. The study highlights the potential of nurse prescribing to enhance patient care and supports the need for health policy planning to integrate this practice into critical care settings.